Biology of the oleander mealybug, Paracoccus burnerae (Brain) (Hemiptera: Pseudococcidae) - Johnson, Todd (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MSc (Botany and Zoology))--University of Stellenbosch, 2010.